Ribbon Proofs for Separation Logic - Wickerson, John; Dodds, Mike; Parkinson, Matthew J. (Proceedings of ESOP, 2013)
We present ribbon proofs, a diagrammatic system for proving program correctness based on separation logic. Ribbon proofs emphasise the structure of a proof, so are intelligible and pedagogical. Because they contain less redundancy than proof outlines, and allow each proof step to be checked locally, they may be more scalable. Where proof outlines are cumbersome to modify, ribbon proofs can be visually manoeuvred to yield proofs of variant programs. This paper introduces the ribbon proof system, proves its soundness and completeness, and outlines a prototype tool for validating the diagrams in Isabelle.